Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
By forming a multi-layered modification layer on the surface of the lithium transition metal composite oxide, the problem of side reaction between the lithium transition metal composite oxide with a high Ni content in the prior art is solved, and the charge and discharge cycle characteristics of the secondary battery are significantly improved.
Patent Information
- Application Number
- CN202380055907.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-06-28
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, nonaqueous electrolyte secondary batteries using lithium transition metal composite oxides with high Ni content rate are prone to side reactions with the nonaqueous electrolyte, resulting in a decrease in charge and discharge cycle characteristics.
A lithium transition metal composite oxide having a layered structure is used, which contains secondary particles formed by the aggregation of primary particles, and a first surface modification layer and a second surface modification layer are present on the surface. The first surface modification layer contains Ca and Sr and other elements, and the second surface modification layer contains elements such as Al, Zr, B, W, Ti, Mg, Co, and Si.
By the presence of the modification layer, side reaction with the non-aqueous electrolyte is suppressed, and the charge and discharge cycle characteristics are significantly improved.
Smart Images

Figure BDA0005255176820000201 
Figure BDA0005255176820000211 
Figure BDA0005255176820000212
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art
[0002] In recent years, the use of non-aqueous electrolyte secondary batteries in power sources for electric vehicles and power storage devices for making full use of natural energy has been expanding. The properties required of the positive electrode active material used in non-aqueous electrolyte secondary batteries also change depending on the use. For example, Patent Document 1 discloses a lithium transition metal composite oxide containing Ca and W in a specified ratio in order to take into account both low-temperature output characteristics and high-temperature cycle characteristics.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2012 / 035664 Summary of the invention
[0006] The initial charge capacity of lithium transition metal composite oxides with a Ni content of 75% or more is large, but they are prone to side reactions with non-aqueous electrolytes, so the charge-discharge cycle characteristics are sometimes reduced. The technology described in Patent Document 1 does not study the improvement of battery characteristics using lithium transition metal composite oxides with a high Ni content, and there is still room for improvement.
[0007] An object of the present disclosure is to provide a positive electrode active material that contributes to improving the charge-discharge cycle characteristics of a non-aqueous electrolyte secondary battery.
[0008] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure is characterized by comprising: x Ni a Co b Mn c M1 d O 2-y(wherein, 0.95≤x≤1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.10, 0≤y<0.05, a+b+c+d=1, and M1 is at least one element selected from the group consisting of W, Mg, Mo, Nb, Ti, Si, Al and Zr), the lithium transition metal composite oxide comprises secondary particles formed by aggregation of primary particles, a first surface modification layer is present on the surface of the primary particles, the first surface modification layer contains at least one element of Ca and Sr and contains at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and a second surface modification layer is present on the surface of the secondary particles, the second surface modification layer contains at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si.
[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by including a positive electrode including the positive electrode active material, a negative electrode, and a nonaqueous electrolyte.
[0010] According to the positive electrode active material for a nonaqueous electrolyte secondary battery as one embodiment of the present disclosure, a nonaqueous electrolyte secondary battery having improved charge and discharge cycle characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. DETAILED DESCRIPTION
[0012] There are transition metal layers and Li layers in the layered structure of the lithium transition metal composite oxide, and the Li ions present in the Li layer reversibly enter and exit, thereby the charge and discharge reaction of the battery is carried out. Generally, lithium transition metal composite oxides of nickel acid lithium system containing Ni as the main component are known as high-capacity positive electrode active materials, and the content of Ni in the lithium transition metal composite oxide is preferably 75 mol% or more relative to the total molar number of metal elements other than Li. In addition, in addition to containing Ni, the lithium transition metal composite oxide may also contain 0 mol% to 15 mol% of Co, 0 mol% to 25 mol% of Mn, and 0 mol% to 10 mol% of M1 (M1 is at least one element selected from W, Mg, Mo, Nb, Ti, Si, Al and Zr) relative to the total molar number of metal elements other than Li. However, by using such a secondary battery of a lithium transition metal composite oxide and a side reaction of a non-aqueous electrolyte, there is a case where the charge and discharge cycle characteristics are reduced.
[0013] Therefore, the inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that: a first surface modification layer containing at least one element selected from Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr is formed on the surface of the primary particles of the lithium transition metal composite oxide, and a second surface modification layer containing at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si is formed on the surface of the secondary particles of the lithium transition metal composite oxide, thereby improving the charge-discharge cycle characteristics. It can be inferred that the secondary particle surface and the first surface modification layer are protected by the second surface modification layer, thereby suppressing the side reaction with the non-aqueous electrolyte and specifically improving the charge-discharge cycle characteristics.
[0014] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is accommodated in a cylindrical outer shell is exemplified, but the electrode body is not limited to the wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through a separator. In addition, the outer shell is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery shell composed of a laminate sheet including a metal layer and a resin layer.
[0015] Figure 1 FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 As shown, the secondary battery 10 includes: a wound electrode body 14, an electrolyte, and an outer shell 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer shell 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer shell 16 is blocked by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer shell 16 is regarded as the lower side.
[0016] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all rectangular strips, and are alternately stacked along the radial direction of the electrode body 14 by spirally winding along the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium precipitation. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and width direction. Two separators 13 are formed to be at least one size larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the end faces of the electrode body 14 in the axial direction.
[0017] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer shell 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer shell 16 by welding or the like, and the outer shell 16 serves as the negative terminal.
[0018] A gasket 28 is provided between the outer shell 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer shell 16, in which a part of the side surface is bulged inwardly and is used to support the sealing body 17. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer shell 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell 16 by the groove portion 22 and the open end of the outer shell 16 that is tightly fitted to the sealing body 17.
[0019] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0020] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , particularly the positive electrode 11 , will be described in detail.
[0021] [positive electrode]
[0022] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.
[0023] The positive electrode mixture layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode mixture slurry including a positive electrode active material, a conductive agent, etc. is applied to the surface of the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby being manufactured.
[0024] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.
[0025] As the binder contained in the positive electrode mixture layer, for example, fluorine resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), etc. can be cited. These can be used alone or in combination of two or more.
[0026] The positive electrode active material contained in the positive electrode mixture layer includes a lithium transition metal composite oxide. In addition, the lithium transition metal composite oxide includes secondary particles formed by the aggregation of primary particles. The particle size of the primary particles constituting the secondary particles of the lithium transition metal composite oxide is, for example, 0.02μm to 2μm. For the particle size of the primary particles, it is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles of the lithium transition metal composite oxide is, for example, 2μm to 30μm. Here, the average particle size refers to the median particle size (D50) based on the volume. D50 refers to the particle size at which the accumulation of frequencies in the volume-based particle size distribution becomes 50% from the particle with the smaller particle size, and is also called the median diameter. The particle size distribution of the secondary particles of the lithium transition metal composite oxide can be measured using a laser diffraction particle size distribution measuring device (for example, Microtrac BEL Corp., MT3000II) with water as the dispersion medium.
[0027] The lithium transition metal composite oxide has a layered structure. As the layered structure of the lithium transition metal composite oxide, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. can be cited. From the viewpoint of high capacity and stability of the crystal structure, the lithium transition metal composite oxide preferably has a layered structure belonging to the space group R-3m. The layered structure of the lithium transition metal composite oxide may include a transition metal layer and a Li layer.
[0028] Lithium transition metal composite oxides are composed of the general formula Li x Ni a Co b Mn c M1 d O 2-y (wherein, 0.95≤x≤1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.10, 0≤y<0.05, a+b+c+d=1, M1 is at least one element selected from the group consisting of W, Mg, Mo, Nb, Ti, Si, Al and Zr). The content of the metal element contained in the lithium transition metal composite oxide is measured, for example, by inductively coupled plasma (ICP) emission spectrometry.
[0029] A high-capacity battery can be obtained by setting the Ni content in the lithium transition metal composite oxide to 75 mol% to 95 mol%. The higher the Ni content, the higher the capacity of the battery.
[0030] The content of Co in the lithium transition metal composite oxide is 0 mol% to 15 mol%, and Co is an arbitrary component. In other words, the lithium transition metal composite oxide may not contain Co. The lithium transition metal composite oxide can improve the heat resistance of the battery by containing Co.
[0031] The content of Mn in the lithium transition metal composite oxide is 0 mol% to 25 mol%, and Mn is an arbitrary component. In other words, the lithium transition metal composite oxide may not contain Mn. The lithium transition metal composite oxide can stabilize the crystal structure by containing Mn.
[0032] The content of M1 (M1 is at least one element selected from the group consisting of W, Mg, Mo, Nb, Ti, Si, Al and Zr) in the lithium transition metal composite oxide is 0 mol% to 10 mol%, and M1 is an arbitrary component. In other words, the lithium transition metal composite oxide may not contain M1.
[0033] There is a first surface modification layer on the surface of the primary particles of the lithium transition metal composite oxide, and the first surface modification layer contains at least one element of Ca and Sr (hereinafter also referred to as "M2") and contains at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr (hereinafter also referred to as "M3"). As a result, the corrosion and degradation of the lithium transition metal composite oxide caused by the side reaction with the non-aqueous electrolyte are effectively suppressed, and the charge and discharge cycle characteristics of the secondary battery 10 are improved. Here, the surface of the primary particle refers to: including the surface of the secondary particle, specifically the surface of the secondary particle and the interface between the primary particles. The first surface modification layer may exist in a dotted manner to cover at least a portion of the surface of the primary particle, or may exist in a manner to cover the entire surface of the primary particle.
[0034] The total amount of M2 contained in the first surface modification layer is preferably 3 mol% or less, more preferably 1 mol% or less, and further preferably 0.5 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. The lower limit of the total amount of M2 is, for example, 0.01 mol%.
[0035] The total amount of M3 contained in the first surface modification layer is 2 mol% or less, more preferably 1 mol% or less, and further preferably 0.5 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. The lower limit of the total amount of M3 is, for example, 0.01 mol%.
[0036] The presence of the first surface modification layer on the surface of the primary particle of the lithium transition metal composite oxide, the presence of the M2 contained in the first surface modification layer, and the presence of the M3 contained in the first surface modification layer can be confirmed by measuring the cross section of the secondary particle of the lithium transition metal composite oxide using TEM-EDX (transmission microscope-energy dispersive X-ray spectrometry). In addition, the total amount of M2 and the total amount of M3 can each be measured by, for example, inductively coupled plasma (ICP) emission spectrometry.
[0037] A compound containing M2 (hereinafter referred to as "M2 compound") and a compound containing M3 (hereinafter referred to as "M3 compound") may be attached to the surface of the primary particles of the lithium transition metal composite oxide. Examples of the M2 compound include oxides, hydroxides, carbonates, etc. containing M2. Examples of the M3 compound include oxides, hydroxides, carbonates, sulfates, etc. containing M3.
[0038] On the surface of the primary particles of the lithium transition metal composite oxide, there may be fixed a substance of the general formula M2 α M3 β O γ(wherein, 1≤α≤2, 1≤β≤5, 4≤γ≤9, M2 is at least one element selected from Ca and Sr, and M3 is at least one element selected from W, Mo, Ti, Si, Nb and Zr) (hereinafter referred to as "M2 α M3 β O γ It should be noted that the M2 compound, the M3 compound, and the M2 compound may coexist on the surface of the primary particles of the lithium transition metal composite oxide. α M3 β O γ Compound.
[0039] M2 α M3 β O γ The presence of the compound can be confirmed using X-ray diffraction analysis. α M3 β O γ The compound may be dispersed on the surface of the primary particles and secondary particles of the lithium transition metal composite oxide, or may exist in a layered manner so as to widely cover the surface of the primary particles and secondary particles. α M3 β O γ The compound is widely present inside and on the surface of the secondary particles. The secondary particles of the lithium transition metal composite oxide may be formed by the aggregation of 5 or more primary particles, and the surface area of the primary particles is larger inside than on the surface of the secondary particles. For example, compared with the surface of the secondary particles, a large amount of M2 is contained inside. α M3 β O γ Compound.
[0040] As M2 α M3 β O γ Specific examples of the compounds include CaWO4, CaMoO3, CaMoO4, CaTiO3, Ca2TiO4, CaSiO3, Ca2SiO4, CaNbO3, CaNb2O6, CaZrO3, CaZr4O9, SrWO4, SrMoO3, SrMoO4, SrTiO3, Sr2TiO4, SrSiO3, Sr2SiO4, SrNbO3, SrNb2O6, SrZrO3, and SrZr4O9.
[0041] There is a second surface modification layer on the surface of the secondary particles of the lithium transition metal composite oxide, and the second surface modification layer contains at least one element (hereinafter referred to as "M4") selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si. Among them, Al, Zr, B, W, Ti and Si are more preferred. The second surface modification layer protects the surface of the secondary particles and the first surface modification layer, so the side reaction with the non-aqueous electrolyte is significantly suppressed, and the charge and discharge cycle characteristics of the secondary battery 10 are further improved. As described below, the second surface modification layer is formed after the first surface modification layer, so on the surface of the secondary particles, the second surface modification layer can also be formed on the first surface modification layer. In addition, the second surface modification layer can exist in a dotted manner in a manner that covers at least a portion of the surface of the secondary particles, or it can exist in a manner that covers the entire surface of the secondary particles.
[0042] The total amount of M4 contained in the second surface modification layer is preferably 2 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. The lower limit of the total amount of M4 is, for example, 0.01 mol%.
[0043] The existence of the second surface modification layer on the surface of the secondary particles of the lithium transition metal composite oxide and the existence of M4 contained in the second surface modification layer can be confirmed by using TEM-EDX to measure the cross section of the secondary particles of the lithium transition metal composite oxide. It should be noted that there is a situation where there is little added M4 raw material, and it is difficult to confirm the existence of the second surface modification layer according to its covering state. At this time, by confirming the existence of the second surface modification layer in the sample with a large amount of M4 raw material addition, it is possible to infer the existence of the second surface modification layer. In addition, the total amount of M4 can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry analysis. In addition, when M3 and M4 are the same element, a simulated sample (dummy Sample) without adding M4 is synthesized at the same time, based on the difference between the measured values of the sample using M3 and M4 as the same element and the simulated sample, the total amount of M3 and the total amount of M4 can be respectively obtained.
[0044] The positive electrode mixture layer may contain other positive electrode active materials in addition to the positive electrode active material of the present embodiment described above. Examples of other positive electrode active materials include lithium transition metal composite oxides having a Ni content of 0 mol % or more and less than 75 mol %.
[0045] Next, an example of a method for producing the positive electrode active material according to the present embodiment will be described.
[0046] The manufacturing process of the positive electrode active material includes the following steps: a first step of mixing a composite oxide and a Li compound to obtain a mixture; a second step of calcining the mixture; and a third step of washing the calcined product with water and heating and drying it. By adding an M2 raw material containing M2 (at least one element selected from Ca and Sr) and an M3 raw material containing M3 (at least one element selected from W, Mo, Ti, Si, Nb and Zr) in the first step, a first surface modification layer containing M2 and M3 can be formed on the surface of the primary particles of the lithium transition metal composite oxide. In addition, by adding an M4 raw material containing M4 (at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si) in the third step, a second surface modification layer containing M4 can be formed on the surface of the secondary particles of the lithium transition metal composite oxide.
[0047] In the first step, for example, a metal oxide, a Li compound, an M2 raw material and an M3 raw material containing 75 mol% to 95 mol% of Ni, 0 mol% to 15 mol% of Co, 0 mol% to 25 mol% of Mn, and 0 mol% to 10 mol% of M1 (M1 is at least one element selected from W, Mg, Mo, Nb, Ti, Si, Al and Zr) are mixed to obtain a mixture.
[0048] The metal oxide is obtained, for example, by stirring a solution of a metal salt containing Ni and any metal element (Co, Mn, etc.), while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to alkaline (e.g., 8.5 to 12.5), precipitating (coprecipitating) a composite hydroxide containing Ni and any metal element, and heat-treating the composite hydroxide, thereby obtaining the metal oxide. There is no particular limitation on the heat treatment temperature, for example, it is in the range of 300°C to 600°C.
[0049] Examples of Li compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. As for the mixing ratio of the metal oxide and the Li compound, from the perspective of facilitating adjustment of the above parameters to the above-specified ranges, for example, the molar ratio of the total amount of the metal element in the metal oxide to Li is preferably in the range of 1:0.98 to 1:1.1.
[0050] As an example of M2 raw materials, Ca(OH)2, CaO, CaCO3, CaSO4, Ca(NO3)2, Sr(OH)2, Sr(OH)2·8H2O, Sr(OH)2·H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc. can be listed, but in order to reduce the amount of moisture generated during roasting, they can also be used after drying and dehydration. In addition, these compounds can also be crushed to a particle size of 0.1 to 20 μm. The same is true for M3 raw materials. Hydroxides, oxides, carbonates, sulfates, nitrates, etc. of M3 (at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr) can be listed, but in order to reduce the amount of moisture generated during roasting, they can also be used after drying and dehydration. In addition, these compounds can also be crushed to a particle size of 0.1 to 20 μm.
[0051] The metal oxide and the M2 raw material are preferably mixed in a ratio of 1:0.0001 to 1:0.03 between the total amount of the metal element in the metal oxide and the molar ratio of the M2 element. When a plurality of M2 raw materials are used, the total amount of M2 contained in the compound is mixed in a manner that satisfies the above ratio. The metal oxide and the M3 raw material are preferably mixed in a ratio of 1:0.0001 to 1:0.02 between the total amount of the metal element in the metal oxide and the molar ratio of the M3 element. When a plurality of M3 raw materials are used, the total amount of M3 contained in the compound is mixed in a manner that satisfies the above ratio.
[0052] In the second step, for example, the mixture is calcined under an oxygen atmosphere to obtain a calcined product. The calcination conditions are that the heating rate from 450°C to 680°C is in the range of more than 1.0°C / minute and less than 5.5°C / minute, and the maximum temperature reached can be in the range of more than 700°C and less than 980°C. The heating rate from more than 680°C to the maximum temperature can be, for example, 0.1°C / minute to 3.5°C / minute. In addition, the holding time to the maximum temperature can be more than 1 hour and less than 10 hours. In addition, the calcination process can be a multi-stage calcination, and if the first heating rate and the second heating rate are within the above-mentioned specified range, multiple temperatures can be set for each temperature zone.
[0053] In the third step, M4 raw material is added to the cake-like composition obtained by washing the above-mentioned calcined product, and heat treatment is performed. Thus, a second surface modification layer containing M4 can be formed on the surface of the secondary particles of the lithium transition metal composite oxide. Washing and heat treatment can be performed in a known method and under conditions. Heat treatment is performed, for example, in a vacuum, in an oxygen gas flow, or in the atmosphere at a temperature of 150°C to 600°C for 1 hour to 5 hours.
[0054] M4 raw material can be added to the cake-like composition before or during heat treatment. As M4 raw materials, for example, tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), boric acid (H3BO3), lithium borate (Li2B4O7, Li3BO3, LiB3O5, LiBO2), aluminum oxide (Al2O3), aluminum sulfate (Al2(SO4)3), zirconium oxide (ZrO2), zirconium sulfate (Zr(SO4)2), titanium oxide (TiO2), titanium hydroxide Ti(OH)4, magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), cobalt oxide (CoO, Co3O4), cobalt sulfate (CoSO4), silicon dioxide (SiO2), silicon monoxide (SiO), etc. In order to effectively modify the surface of the secondary particles, as M4 raw materials, oxides and metal salts soluble in alkaline water containing the Li salt contained in the cake-like composition are more preferably included. In addition, the M4 raw material can be added not only in solid form, but also dissolved in an acid or the like to prepare an aqueous solution and added. The addition method can be dripped or sprayed into the cake-like composition, and spraying is preferably performed in order to effectively cover the surface of the secondary particles. Furthermore, in order to effectively cover the surface of the secondary particles, the M4 raw material can also be added to the lithium transition metal composite oxide after washing and heat treatment instead of the cake-like composition obtained by washing, and then calcined again in a vacuum, in an oxygen gas flow, and in the atmosphere at a temperature of 150°C to 600°C for 1 to 5 hours.
[0055] The amount of M4 raw material added is adjusted to a ratio of 0.01 mol% to 2 mol% relative to the total molar amount of metal elements other than Li contained in the metal oxide. When using multiple M4 raw materials, the total amount of M4 added is added to satisfy this ratio.
[0056] [negative electrode]
[0057] The negative electrode 12, for example, has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. As the negative electrode collector, a foil of a metal such as copper or copper alloy that is stable within the potential range of the negative electrode 12, a thin film having the metal disposed on the surface, etc. can be used. The thickness of the negative electrode collector is, for example, 5 μm to 30 μm. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode collector. The negative electrode 12 can be made, for example, as follows: a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is applied to the surface of the negative electrode collector, and after the coating is dried, it is rolled to form a negative electrode mixture layer on both sides of the negative electrode collector, thereby making it possible to make it.
[0058] As the negative electrode active material contained in the negative electrode mixture layer, there is no particular limitation as long as it can reversibly store and release lithium ions, and carbon materials such as graphite are usually used. The graphite can be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, massive artificial graphite, graphitized mesophase carbon microbeads, etc. In addition, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can be used. In addition, those provided with a carbon coating film can be used. For example, SiO x (0.5 ≤ x ≤ 1.6) of the Si-containing compound, or Li 2y SiO (2+y) (0 < y < 2) of the lithium silicate phase in which fine particles of Si are dispersed, such as Si-containing compounds, are used in combination with graphite.
[0059] As the binder contained in the negative electrode mixture layer, for example, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (which can be PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone as 1 kind, or 2 or more kinds can be used in combination.
[0060] [Separator]
[0061] In the separator 13, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can have a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as aromatic polyamide resin, a filler layer containing a filler of an inorganic compound can be provided on the surface of the separator 13.
[0062] [Non-aqueous electrolyte]
[0063] The non-aqueous electrolyte contains, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. In the non-aqueous solvent, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of 2 or more of them can be used. The non-aqueous solvent can contain a halogen-substituted body obtained by substituting at least a part of the hydrogen atoms of these solvents with halogen atoms such as fluorine. As the halogen-substituted body, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylic esters such as methyl fluoropropionate (FMP), etc. can be cited.
[0064] Examples of the above esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL), γ-valerolactone (GVL); and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, etc.
[0065] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ethers; and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.
[0066] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (CnF 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2); imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, etc. The lithium salt can be used alone or in combination of multiple kinds. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., LiPF6 is preferably used. The concentration of the lithium salt is, for example, 0.5 mol to 2 mol per 1 L of the non-aqueous solvent. In addition, vinylene carbonate, propanesultone-based additives can be further added.
[0067] Example
[0068] Hereinafter, the present disclosure will be further described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0069] <Example 1-1>
[0070] [Preparation of positive electrode active material]
[0071] The [Ni 0.90 Co 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.90 Co 0.05 Mn 0.05 Next, lithium oxide, the metal oxides, calcium hydroxide and tungsten oxide are mixed in such a manner that the molar ratio of the total amount of Li, Ni, Co and Mn to Ca and W is 1.03:1:0.0025:0.005 to obtain a mixture (first step). The mixture is heated under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture is calcined from room temperature to 650°C at a heating rate of 2.0°C / min and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a calcined product (the second step). Water is added to the calcined product so that the slurry concentration becomes 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition. Powdered H3BO3 is added to the cake-like composition. The amount of H3BO3 added is adjusted in such a way that the molar ratio of B becomes 0.1 mol% relative to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide. After the addition step, a drying step is carried out under a vacuum atmosphere at 180°C for 2 hours to obtain the positive electrode active material of Example 1 (the third step).
[0072] The obtained positive electrode active material was measured by an ICP emission spectrometer (Thermo Fisher Scientific, iCAP6300), and the results confirmed that the elements shown in Table 1 described later were elements other than Li, O and impurity elements. In addition, by TEM-EDX, it was confirmed that there was a first surface modification layer containing Ca and W at the interface between the primary particles on the surface of the secondary particles and the inside of the secondary particles. By radiated light X-ray diffraction measurement, the compounds present in the first surface modification layer were identified, and the presence of CaWO4 was confirmed. In addition, by TEM-EDX, it was confirmed that there was a second surface modification layer containing B on the surface of the secondary particles.
[0073] [Production of positive electrode]
[0074] 95 parts by mass of the above-mentioned positive electrode active material are mixed with 3 parts by mass of acetylene black (AB) and 2 parts by mass of polyvinylidene fluoride (PVDF), and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of the positive electrode collector formed by aluminum foil, and after the coating is dried, the coating is rolled using a calendering roller, cut into a specified electrode size, and a positive electrode is made. It should be noted that a portion of the positive electrode is provided with an exposed portion exposed on the surface of the positive electrode collector.
[0075] [Production of negative electrode]
[0076] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of a negative electrode collector formed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to produce a negative electrode. It should be noted that a portion of the negative electrode is provided with an exposed portion where the surface of the negative electrode collector is exposed.
[0077] [Preparation of non-aqueous electrolyte]
[0078] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0079] [Production of test battery cells]
[0080] A positive electrode lead is installed on the exposed part of the positive electrode, and a negative electrode lead is installed on the exposed part of the negative electrode. The positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator interposed therebetween, and then press-formed in the radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate sheet, and after the above-mentioned non-aqueous electrolyte is injected, the opening of the outer shell is sealed to obtain a test battery cell.
[0081] [Evaluation of capacity maintenance rate]
[0082] At an ambient temperature of 25°C, the test battery cell was charged at a constant current of 0.2 It until the battery voltage reached 4.3 V, and then charged at a constant voltage of 4.3 V until the current value reached 0.01 It. Then, it was discharged at a constant current of 0.2 It until the battery voltage reached 2.5 V. This charge and discharge was regarded as one cycle, and 30 cycles were performed. The capacity retention rate of the test battery cell in the charge and discharge cycle was calculated according to the following formula.
[0083] Capacity retention rate = (discharge capacity at the 30th cycle / discharge capacity at the 1st cycle) × 100
[0084] <Examples 1-2 to 1-4>
[0085] In the third step of preparing the positive electrode active material, the amount of H3BO3 added was adjusted so that the molar ratio of B became 0.5 mol%, 1.0 mol%, and 2.0 mol%, respectively. A test cell was prepared and evaluated in the same manner as in Example 1-1.
[0086] <Example 1-5>
[0087] In the third step of preparing the positive electrode active material, Al2(SO4)3·16H2O (hereinafter, hydration water is omitted and recorded as Al2(SO4)3) is added instead of H3BO3, and the amount of Al2(SO4)3 added is adjusted so that the molar ratio of Al to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide becomes 0.1 mol%. Otherwise, a test battery cell is prepared and evaluated in the same manner as in Example 1. By TEM-EDX, it is confirmed that a second surface modification layer containing Al exists on the surface of the secondary particles.
[0088] <Examples 1-6 to 1-8>
[0089] In the third step of preparing the positive electrode active material, the addition amount of Al2(SO4)3 was adjusted so that the molar ratio of Al became 0.5 mol%, 1.0 mol% and 2.0 mol%, respectively. Except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-5.
[0090] <Example 1-9>
[0091] In the third step of preparing the positive electrode active material, Zr(SO4)2·4H2O (hereinafter, hydration water is omitted and recorded as Zr(SO4)2) is added instead of H3BO3, and the amount of Zr(SO4)2 added is adjusted so that the molar ratio of Zr to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide becomes 0.1 mol%. Otherwise, a test battery cell is prepared and evaluated in the same manner as in Example 1-1. By TEM-EDX, it is confirmed that a second surface modification layer containing Zr exists on the surface of the secondary particles.
[0092] <Examples 1-10 to 1-12>
[0093] In the third step of preparing the positive electrode active material, the added amount of Zr(SO4)2 was adjusted so that the molar ratio of Zr became 0.5 mol%, 1.0 mol% and 2.0 mol%, respectively. Except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-9.
[0094] <Example 1-13>
[0095] In the third step of preparing the positive electrode active material, WO3 is added instead of H3BO3, and the amount of WO3 added is adjusted so that the molar ratio of W to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide becomes 0.1 mol%. Otherwise, the test battery cell is prepared in the same manner as in Example 1-1 and evaluated. By TEM-EDX, it is confirmed that there is a second surface modification layer containing W on the surface of the secondary particles. It should be noted that by TEM-EDX, it is confirmed that: the first surface modification layer is formed on the surface of the secondary particles, and the second surface modification layer is formed on the surface of the secondary particles on the first surface modification layer.
[0096] <Examples 1-14 to 1-16>
[0097] In the third step of preparing the positive electrode active material, the amount of WO 3 added was adjusted so that the molar ratio of W became 0.5 mol %, 1.0 mol %, and 2.0 mol %, respectively. A test cell was prepared and evaluated in the same manner as in Example 1-13.
[0098] <Example 1-17>
[0099] In the third step of preparing the positive electrode active material, a 30% by mass titanium sulfate (Ti(SO4)2) aqueous solution was added instead of H3BO3, and the amount of titanium sulfate aqueous solution added was adjusted so that the molar ratio of Ti to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide was 0.1 mol%. A test battery cell was prepared and evaluated in the same manner as in Example 1-1. By TEM-EDX, it was confirmed that a second surface modification layer containing Ti existed on the surface of the secondary particles.
[0100] <Examples 1-18 to 1-20>
[0101] In the third step of preparing the positive electrode active material, the amount of the titanium sulfate aqueous solution added was adjusted so that the molar ratio of Ti became 0.5 mol%, 1.0 mol%, and 2.0 mol%, respectively. A test cell was prepared and evaluated in the same manner as in Example 1-17.
[0102] <Comparative Example 1-1>
[0103] A test cell was produced and evaluated in the same manner as in Example 1-1 except that H 3 BO 3 was not added in the third step of producing the positive electrode active material.
[0104] <Comparative Example 1-2>
[0105] In the first step of preparing the positive electrode active material, Ca(OH)2 and WO3 were not added. In the third step of preparing the positive electrode active material, the amount of H3BO3 added was adjusted so that the molar ratio of B became 0.5 mol%. Otherwise, a test battery cell was prepared and evaluated in the same manner as Example 1-1.
[0106] <Comparative Examples 1-3>
[0107] In the first step of preparing the positive electrode active material, Ca(OH)2 and WO3 were not added. In the third step of preparing the positive electrode active material, Al2(SO4)3 was added instead of H3BO3, and the amount of Al2(SO4)3 added was adjusted so that the molar ratio of Al to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide became 0.5 mol%. Otherwise, a test battery cell was prepared and evaluated in the same manner as Example 1-1.
[0108] <Comparative Example 1-4>
[0109] In the first step of preparing the positive electrode active material, Ca(OH)2 and WO3 were not added. In the third step of preparing the positive electrode active material, Zr(SO4)2 was added instead of H3BO3, and the amount of Zr(SO4)2 added was adjusted so that the molar ratio of Zr to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide became 0.5 mol%. Otherwise, a test battery cell was prepared and evaluated in the same manner as Example 1-1.
[0110] <Comparative Example 1-5>
[0111] In the first step of preparing the positive electrode active material, Ca(OH)2 and WO3 were not added. In the third step of preparing the positive electrode active material, WO3 was added instead of H3BO3, and the amount of WO3 added was adjusted so that the molar ratio of W relative to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide became 0.5 mol%. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.
[0112] <Comparative Example 1-6>
[0113] In the first step of preparing the positive electrode active material, Ca(OH)2 and WO3 were not added. In the third step of preparing the positive electrode active material, an aqueous solution of titanium sulfate was added instead of H3BO3, and the amount of the aqueous solution of titanium sulfate added was adjusted so that the molar ratio of Ti relative to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide became 0.5 mol%. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.
[0114] <Comparative Example 1-7>
[0115] A test cell was produced and evaluated in the same manner as in Example 1-1 except that Ca(OH) 2 and WO 3 were not added in the first step of producing the positive electrode active material, and H 3 BO 3 was not added in the third step.
[0116] <Examples 2-1 to 2-5, Comparative Example 2-1>
[0117] In the first step of preparing the positive electrode active material, the amount of Ca(OH)2 added was adjusted so that the molar ratio of Ca was 0.5 mol%, and the test battery cells were prepared and evaluated in the same manner as in Examples 1-2, 1-6, 1-10, 1-14, 1-18 and Comparative Example 1-1. The compounds present in the first surface modification layer were identified by X-ray diffraction measurement, and the presence of CaWO4 was confirmed.
[0118] <Examples 3-1 to 3-5, Comparative Examples 3-1 to 3-7>
[0119] The composition of the metal oxide used in the first step of preparing the positive electrode active material was changed to Ni 0.90 Co 0.03 Mn 0.07 O2, and except for this, test cells were prepared and evaluated in the same manner as in Examples 1-2, 1-6, 1-10, 1-14, 1-18 and Comparative Examples 1-1 to 1-7.
[0120] <Examples 4-1 to 4-5, Comparative Example 4-1>
[0121] In the first step of making the positive electrode active material, Sr(OH)2 is added instead of Ca(OH)2, and the amount of Sr(OH)2 added is adjusted in such a way that the molar ratio of Sr to the total amount of Ni, Co and Mn contained in the lithium transition metal composite oxide becomes 0.25 mol%. Otherwise, the test battery cells are made in the same manner as in Examples 1-2, 1-6, 1-10, 1-14, 1-18 and Comparative Example 1-1, and evaluated. By TEM-EDX, it was confirmed that there was a first surface modification layer containing Sr and W on the surface of the secondary particles and at the interface between the primary particles in the interior of the secondary particles. The compounds present in the first surface modification layer were identified by radiation light X-ray diffraction measurement, and the presence of SrWO4 was confirmed.
[0122] <Examples 5-1 to 5-5, Comparative Examples 5-1 to 5-7>
[0123] The composition of the metal oxide used in the first step of preparing the positive electrode active material was changed to Ni 0.80 Co 0.10 Mn 0.10 O2, and except for this, test cells were prepared and evaluated in the same manner as in Examples 1-2, 1-6, 1-10, 1-14, 1-18 and Comparative Examples 1-1 to 1-7.
[0124] The capacity maintenance rates of the test battery cells of the examples and comparative examples are shown in Table 1. In addition, Table 1 also shows the composition of the lithium transition metal composite oxide, the addition amounts of Ca or Sr and W in the first step, and the elements and addition amounts added in the third step. The capacity maintenance rates of the test battery cells of Examples 1-1 to 1-20 and Comparative Examples 1-1 to 1-6 shown in Table 1 are expressed relative to the capacity maintenance rate of the test battery cell of Comparative Example 1-7 as 100. The capacity maintenance rates of the test battery cells of Examples 2-1 to 2-5 and Comparative Example 2-1 shown in Table 2 are expressed relative to the capacity maintenance rate of the test battery cell of Comparative Example 1-7 as 100. The capacity maintenance rates of the test battery cells of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-6 shown in Table 3 are expressed relative to the capacity maintenance rate of the test battery cell of Comparative Example 3-7 as 100. The capacity maintenance rates of the test cells of Examples 4-1 to 4-5 and Comparative Example 4-1 shown in Table 4 are expressed relative to the capacity maintenance rate of the test cells of Comparative Example 1-7 being 100. The capacity maintenance rates of the test cells of Examples 5-1 to 5-5 and Comparative Examples 5-1 to 5-6 shown in Table 5 are expressed relative to the capacity maintenance rate of the test cells of Comparative Example 5-7 being 100.
[0125] [Table 1]
[0126]
[0127] [Table 2]
[0128]
[0129] [Table 3]
[0130]
[0131] [Table 4]
[0132]
[0133] [Table 5]
[0134]
[0135] In each of Tables 1 to 5, the test battery cell of the embodiment has a higher capacity retention rate than the test battery cell of the comparative example. Therefore, it can be seen that: in the lithium transition metal composite oxide having a predetermined composition, a first surface modification layer containing at least one element selected from Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr is formed on the surface of the primary particles, and a second surface modification layer containing at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si is formed on the surface of the secondary particles, thereby improving the charge and discharge cycle characteristics.
[0136] The present disclosure will be further described based on the following embodiments.
[0137] Composition 1:
[0138] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a layered structure and a general formula Li x Ni a Co b Mn c M1 d O 2-y (wherein, 0.95≤x≤1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.10, 0≤y<0.05, a+b+c+d=1, and M1 is at least one element selected from the group consisting of W, Mg, Mo, Nb, Ti, Si, Al and Zr) represented by a lithium transition metal composite oxide,
[0139] The lithium transition metal composite oxide includes secondary particles formed by aggregation of primary particles.
[0140] A first surface modification layer exists on the surface of the primary particle, wherein the first surface modification layer contains at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.
[0141] A second surface modification layer exists on the surface of the secondary particle, and the second surface modification layer contains at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si.
[0142] Composition 2:
[0143] According to the positive electrode active material for a non-aqueous electrolyte secondary battery as described in Configuration 1, the total amount of Ca and Sr contained in the first surface modification layer is 3 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide.
[0144] Composition 3:
[0145] According to the positive electrode active material for a non-aqueous electrolyte secondary battery as described in configuration 1 or 2, the total amount of W, Mo, Ti, Si, Nb and Zr contained in the aforementioned first surface modification layer is less than 2 mol% relative to the total molar amount of metal elements other than Li in the aforementioned lithium transition metal composite oxide.
[0146] Composition 4:
[0147] A positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of structures 1 to 3, wherein the total amount of Al, Zr, B, W, Ti, Mg, Co and Si contained in the aforementioned second surface modification layer is less than 2 mol% relative to the total molar amount of metal elements other than Li in the aforementioned lithium transition metal composite oxide.
[0148] Composition 5:
[0149] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of configurations 1 to 4, wherein a particle of the general formula M2 is fixed on the surface of the primary particle α M3 β O γ (wherein, 1≤α≤2, 1≤β≤5, 4≤γ≤9, M2 is at least one element selected from Ca and Sr, and M3 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr).
[0150] Composition 6:
[0151] A nonaqueous electrolyte secondary battery comprises: a positive electrode containing the positive electrode active material for a nonaqueous electrolyte secondary battery according to any one of configurations 1 to 5, a negative electrode, and a nonaqueous electrolyte.
[0152] Description of Reference Numerals
[0153] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer shell, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a layered structure having a general formula Li x Ni a Co b Mn c M1 d O 2-y The lithium transition metal composite oxide shown in the formula, wherein 0.95≤x≤1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.10, 0≤y<0.05, a+b+c+d=1, M1 is at least one element selected from the group consisting of W, Mg, Mo, Nb, Ti, Si, Al and Zr, The lithium transition metal composite oxide includes secondary particles formed by aggregation of primary particles, A first surface modification layer is present on the surface of the primary particle, the first surface modification layer containing at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, A second surface modification layer exists on the surface of the secondary particle, and the second surface modification layer contains at least one element selected from the group consisting of Al, Zr, B, W, Ti, Mg, Co and Si.
2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The total amount of Ca and Sr contained in the first surface modification layer is 3 mol % or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide.
3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The total amount of W, Mo, Ti, Si, Nb and Zr contained in the first surface modification layer is 2 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide.
4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The total amount of Al, Zr, B, W, Ti, Mg, Co and Si contained in the second surface modification layer is 2 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide.
5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein On the surface of the primary particles, there is fixed a substance of the general formula M2 α M3 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M2 is at least one element selected from Ca and Sr, and M3 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. 6 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Fuel nozzle and filler tube system adapted for robotic refueling systems
WO2001040105A1
Data communication system
WO2001060107A2
Lithium ion secondary battery
WO2012035664A1